2010
DOI: 10.1590/s0034-71672010000100015
|View full text |Cite
|
Sign up to set email alerts
|

Competências gerenciais na formação do enfermeiro

Abstract: This study had as purpose to identify the insertion of the management competences in the formation of nurses. That was a study of qualitative approach, that used the analysis of content of the pedagogic documents of the course of nursing of an institution of higher education of the South Region of the country. In the thematic documental analysis developed in this study, the evidence of the meaning items corroborated the insert of the managerial competence in the dimensions: knowledge, abilities and attitudes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
26

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 3 publications
0
11
0
26
Order By: Relevance
“…Management competences in the formation of nurses. Lourencao DC, Benito GA (18) To identify the insertion of management competencies in nursing training.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Management competences in the formation of nurses. Lourencao DC, Benito GA (18) To identify the insertion of management competencies in nursing training.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, the use of pedagogical methods that allow recognition of users as singular individuals, and that allow for experience and development of leadership skills, will provide the foundation for nurses to engage in interdisciplinarity. (18,28) The complexity of health care refers to the need for interdisciplinary work through sharing knowledge, responsabilities and decisions, in order to overcome interdisciplinary barriers and achieve care comprehensiveness. (18) Nevertheless, studies have shown that in undergraduate courses, teaching spaces are still focused mainly on clinical practice, especially the healing field; the predominant approach is biological, with a significant dissociation between theory and practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the clinical patient file and other forms required by the Ministry of Health, with data essential to plan, follow-up and assess disease control 3 . However, this multiplicity of forms can lead to data duplication or failure to record data, and vulnerabilities in using this data to subsidize decisions that must be made on a daily basis as part of routine healthcare 4 .…”
Section: Introductionmentioning
confidence: 99%